The Impact of COVID-19 in Europe: A Comprehensive Analysis - Benvolio Dante (GoAcademica Research & Publishing, 2023)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has had a profound impact on the European continent. This scientific journal article aims to provide a comprehensive analysis of the spread, healthcare response, socio-economic consequences, and lessons learned from the COVID-19 pandemic in Europe. It combines data-driven insights with a review of relevant scientific literature to present a holistic view of the situation in Europe